2021
DOI: 10.1108/jd-03-2021-0065
|View full text |Cite
|
Sign up to set email alerts
|

Workplace information literacy: a bridge to the development of innovative work behaviour

Abstract: PurposeOrganisational culture and leadership, employee skills and aptitudes, access to resources, and training are regularly cited as important determinants of the development of innovative work behaviour (IWB). The purpose of the work reported in this paper was to investigate a further set of possible determinants of the development of IWB: those that are information-related.Design/methodology/approachA mixed methods approach was adopted. Quantitative and qualitative data were collected by questionnaire, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 71 publications
(84 reference statements)
2
19
0
Order By: Relevance
“…However, the mentioned studies were conducted in different settings compared to the industries, organisational size and country context. In addition, the findings of this study are also in line with those of Middleton and Hall (2021), who found a positive influence of informal learning (Innovative learning and knowledge sharing) of different stages of IWB including creation of new OE, IG and IP. Information sharing to IG, IP and IR stages and innovative learning was related to IG and IP stages.…”
Section: Findings and Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, the mentioned studies were conducted in different settings compared to the industries, organisational size and country context. In addition, the findings of this study are also in line with those of Middleton and Hall (2021), who found a positive influence of informal learning (Innovative learning and knowledge sharing) of different stages of IWB including creation of new OE, IG and IP. Information sharing to IG, IP and IR stages and innovative learning was related to IG and IP stages.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…The fifth dimension i.e. reflection, is about the assessment of the innovation process, evaluation of the activities and personal advancement during the innovation process (Middleton & Hall, 2021). In the current study, the first four dimensions of this model are considered to explain the process of IWB among knowledge workers of SMEs.…”
Section: Reflection (Ref)mentioning
confidence: 99%
See 3 more Smart Citations